Renin-Angiotensin-Aldosterone Profiles in Pregnant Women With Chronic Hypertension. Issue 2 (August 2018) - Malha, Line; Sison, Cristina P.; Helseth, Geraldine; Sealey, Jean E.; August, Phyllis
Abstract : Pregnant women with chronic hypertension are at risk for increased blood pressure and superimposed preeclampsia (SPE) in late pregnancy. Alterations in the renin-aldosterone system are a feature of normal pregnancy; however, their role in chronic hypertension with and without SPE is less clear. We performed a prospective, longitudinal trial of 108 women with chronic hypertension and measured plasma renin activity (PRA), 24-hour urine sodium, urine potassium, and urine aldosterone (Ualdo) at 12, 20, 28, and 36 weeks and postpartum. SPE developed in 34% of pregnancies. PRA was lower in women who developed SPE at weeks 28 (5.99 versus 6.22 ng/mL per hour; P <0.001) and 36 (5.71 versus 7.74 ng/mL per hour; P =0.002). Ualdo was lower in women with SPE compared with those without SPE at 28 weeks (59.6 versus 81.3 μg/d; P =0.039). Mean arterial pressure was inversely related to both PRA ( r =−0.23; P <0.0001) and Ualdo ( r =−0.11; P =0.029). PRA and Ualdo were positively associated with each other ( r =0.5327; P <0.0001) after adjusting for urine potassium, urine sodium, serum potassium, and mean arterial pressure. PRA and Ualdo were lower in women of black race compared with other racial groups ( P <0.001). Our results demonstrate that in women with chronic hypertension PRA and Ualdo increase in early pregnancy and subsequently decrease in women who develop SPE. These findings are consistent with the hypothesis that sodium retention may contribute to the elevation in blood pressure in SPE. Abstract : Supplemental Digital Content is available in the text.